2011
DOI: 10.1111/j.1472-765x.2011.03159.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and microbial diversity of palm oil mill effluent microbial fuel cell

Abstract: Aim:  To evaluate the bioenergy generation and the microbial community structure from palm oil mill effluent using microbial fuel cell. Methods and Results:  Microbial fuel cells enriched with palm oil mill effluent (POME) were employed to harvest bioenergy from both artificial wastewater containing acetate and complex POME. The microbial fuel cell (MFC) showed maximum power density of 3004 mW m−2 after continuous feeding with artificial wastewater containing acetate substrate. Subsequent replacement of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 38 publications
2
9
0
1
Order By: Relevance
“…The maximum power generated was 45 mW/m 2 with 45% of COD removal in 15 days. The microbial community structure from palm oil mill effluent in MFC have also been studied (Jong et al, 2011) in which electrochemically-active bacterial consortium was successfully enriched from POME in the anode chamber under anaerobic condition. Analysis using 16S rDNA showed that 88.5% of the community was from the group Deltaproteobacteria while members of Gammaproteobacteria, Epsilonproteobacteria and Betaproteobacteria codominated the microbial consortium.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum power generated was 45 mW/m 2 with 45% of COD removal in 15 days. The microbial community structure from palm oil mill effluent in MFC have also been studied (Jong et al, 2011) in which electrochemically-active bacterial consortium was successfully enriched from POME in the anode chamber under anaerobic condition. Analysis using 16S rDNA showed that 88.5% of the community was from the group Deltaproteobacteria while members of Gammaproteobacteria, Epsilonproteobacteria and Betaproteobacteria codominated the microbial consortium.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the use of carbon-based electrodes as components for electron transfers in MFCs. These include carbon cloth (Ishi et al 2012), graphite fibre brush (Yang et al 2013), and graphite felt (Jong et al 2011). However, no study has examined the potential of rice husk as a workable source of electrode material for electricity generation in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…The selection is due to the high current density and power density it can produce. The voltage produces by river, animal waste and palm oil effluent is 0.6-0.9 V, 0.6-0.8 V and 0.75-0.80 V respectively [4][5][6].…”
Section: Introductionmentioning
confidence: 99%